2019
DOI: 10.3389/fped.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Precocious and Early Central Puberty in Children With Pre-existing Medical Conditions: A Single Center Study

Abstract: Background: Precocious and early puberty are reported findings in children with pre-existing medical conditions including certain syndromes. Series pertaining to such situations are limited. Methods: A retrospective, single-center study was conducted on children with central precocious puberty (onset before the age of 8 years in girls and 9 years in boys) or early puberty (onset between 8 and 9 years in girls and between 9 and 10.5 years in boys) diagnosed on the background o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…The PROS study reported a downward trend in pubertal onset in females [Herman-Giddens et al, 1997] suggesting that standards need to be redefined in order to provide appropriate education and care by professionals and parents alike. Historically, precocious puberty (onset <8 years in females and 9 years in males) or early puberty (onset between 8 and 9 years in females and between 9 and 10.5 years in males) can be considered a normal variant [Winter, Durand, & Brauner, 2019]. A portion of the females with ASD would likely meet criteria for precocious puberty and an even larger proportion would meet criteria for early puberty.…”
Section: Discussionmentioning
confidence: 99%
“…The PROS study reported a downward trend in pubertal onset in females [Herman-Giddens et al, 1997] suggesting that standards need to be redefined in order to provide appropriate education and care by professionals and parents alike. Historically, precocious puberty (onset <8 years in females and 9 years in males) or early puberty (onset between 8 and 9 years in females and between 9 and 10.5 years in males) can be considered a normal variant [Winter, Durand, & Brauner, 2019]. A portion of the females with ASD would likely meet criteria for precocious puberty and an even larger proportion would meet criteria for early puberty.…”
Section: Discussionmentioning
confidence: 99%
“…↑/↓ denotes higher/lower steroid or steroid ratio in ASD group compare to control group; ASD, autism spectrum disorder; C, conjugate; CTRL, control; S, sulfate; NA, hormone not assessed; (↑/↓), non-significant difference ↑/↓ significant difference between CTRL and ASD in favor to ASD with p value up to p = 0.2 according to the results presented in Tables 1 and 2. etiocholanolone, androstenediol, 11β-hydroxyandrosterone, 11β-hydroxyetiocholanolone, DHEA, 5-androstene-3β, 17β-diol in ASD compared to CTRL. This fact might be explained by precocious adrenarche leading to premature puberty described even in individuals having ASD 13,25 . Gasser et al analyzed steroid pathway in pubertal individuals, thus, sexual maturity have to be critically taken into account 12 .…”
Section: Discussionmentioning
confidence: 99%
“…They observed significantly higher level of most of the measured androstanes like androsterone, etiocholanolone, androstenediol, 11β-hydroxyandrosterone, 11β-hydroxyetiocholanolone, DHEA, 5-androstene-3β, 17β-diol in ASD compared to CTRL. This fact might be explained by precocious adrenarche leading to premature puberty described even in individuals having ASD 13 , 25 . Gasser et al analyzed steroid pathway in pubertal individuals, thus, sexual maturity have to be critically taken into account 12 .…”
Section: Discussionmentioning
confidence: 99%
“…DLK1 loss-of-function mutations determine a more complex, yet infrequent phenotype characterized by CPP, overweight, early Type 2 Diabetes, hyperlipidemia and Polycistic Ovary Syndrome (7). Besides that, rare cases of patients with CPP primarily related to clinical syndromes or chromosomal abnormalities have been identi ed (8).…”
Section: Introductionmentioning
confidence: 99%